Pengaruh Leverage Dan Volatilitas Laba Terhadap Volatilitas Harga Saham Pada Sektor Properties dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Fatimatuzzahra, Siti; Tri Kusumawati, Yulia; Anshari, Rahman (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to examine the effect of leverage and earnings volatility on stock price volatility in the property and real estate sector listed on the Indonesia Stock Exchange during the 2023–2024 period. This sector plays a key role in national economic development but remains vulnerable to market fluctuations. Using a quantitative approach, the study involved a population of 94 companies and selected 77 companies as samples through purposive sampling. Data were collected using documentation methods from annual financial reports available on the Indonesia Stock Exchange and company websites. The analysis employed multiple linear regression. The results show that leverage has no significant effect on stock price volatility. On the other hand, earnings volatility has a significant and negative effect, indicating that higher earnings fluctuations tend to lower stock price volatility. These findings support signaling theory and offer valuable insights for investors, corporate managers, and regulators in understanding market risk behavior. However, the model explains only 2.4% of the variation in stock prices, suggesting the need for further research with broader variables and a longer time horizon.